PENGUJIAN ASAM LEMAK BEBAS PADA WAJIK YANG DILAPISI EDIBLE FILM KHITOSAN-PVA - Eddwina Aidila Fitria; I Ketut Budaraga; Samudera Zebua (SAGU, 2022)
Wajik is one of the traditional snacks that many people are interested in sweet and legit mandatory tastes that further add to consumer interest in this product. This product is a semi-wet food made from glutinous rice, coconut milk, coconut and sugar. Coconut milk is a mandatory additive in making wajik, because the oil produced by coconut milk will bring out a legit taste and savory. Coconut milk also produces fat in wajik. Fat contained in wajik make this product have a short shelf life because it is easy to experience rancidity. Plastic is one of the packaging that is often used to package this product to reduce the use of plastic, so it can be replaced with edible chitosan -PVA film. The purpose of this study is to determine the value of free fatty acids in Wajik coated edible Chitosan-PVA film until it reaches damage. This study used a complete randomized design with 5 levels of treatment and 3 repeats. A data as deep as the analysis was analyzed using ANOVA and test continued DNMRT at a real level of 1%. The treatment in this study is wajik storage period coated with edible chitosan-PVA film (0, 5, 10, 15, 20 Days). The results showed that edible film had a very noticeable effect on the wajik characteristics based on the free fatty acid test. The value of free fatty acids on Wajik on storage day-0 (0.02%), day-5 (0.04%), day-10 (0.06%), day-15 (0.12%) and day-20 (0.16%). Based on this SNI 01-4272-1996, wajik coated edible chitosan-PVA film can last until the tenth day.